Management of water Issues in Taiz basin, Yemen - Al-Kebsi, Al Khateeb Y.; Matraf, Abdulrahman M. Ba; AL-Dubai, Mohamed F. M. (Thamar University Journal of Natural & Applied Sciences, 2023)
Generally, the study area including the city of Taiz, in particular is suffering from an acute shortage of water due to the increase of the growing demand on water for domestic and industrial needs as well as the water needs for agriculture in the region. In addition, the water resources in the study area are limited to the aquifers while water extraction rates exceed the natural recharge and the use is not effective. Therefore, it highlights the importance of water demand management to maintain the quantity and quality of drinking water and domestic use, irrigation and industry. The objectives of this study is to evaluate current and future vulnerability of water sources in the study area; Development of scenarios and analysis of future water balance to find out the best solution to the problem of water in Taiz basin as the study area; Select the appropriate scenario to resolve the water problem. The results of this study will assist decision makers in the field of water resources for better planning and management in the future. During the period 15/1/2013 to 15/4/2013 Implementation of the field study in 1501water points, these water points are distributed between 954 hand-dug well, 479 deep well, 50 springs, five water collection tanks, two dams, and six water retaining walls. For calculating the amount of water supply in the region and the amount of water deficit, in addition to knowing the amount of needs that must be secured in the future, Water Evaluation And Planning (WEAP) application as Decision Support System (DSS) to manage the supply and demand for water in Taiz basin as the study area. The analysis and results using WEAP program include the following themes: Ground water storage in the aquifers: The usable storage for the base year of the model (2013) has been calculated for the five sub-basins in the study area, Estimated ground water storage in alluvial aquifer (in Mm3) ranged 221.52-415.36 Mm3 at best estimate at 332.29 Mm3, groundwater storage in Volcanic aquifer ranged 129.98-2599.52 Mm3 at best estimate 259.95, whereas groundwater storage in sandstone aquifer ranged 5.044- 50.44Mm3 at best estimate at 10.088; Unmet water demand, The gap between supply and demand for water in the study area was estimated as (47,692,840.9 m3). Preliminary, set of adaptation strategies that address water scarcity; Interpret the proposed set of adaptation strategies to solve water issue from improve water services and water management for the urban area as part of the study in Central and Al Hawban Sub Catchment:(Increase the coverage rates for water services, Diversify water sources for the city, Efficient water management, Implementation of control and water quality program in water sources and drinking water factories, Development of specialized human cadres technically and administratively for the development of water management, Flow of water services from different water sources….. etc.); and Improve water projects and water management for the rural area as part of the study area Al Dabab Sub Catchment, Al Janad Sub Catchment and Thi- Sufal Al Haimah Sub Catchment: Commitment of the Commission basin management to Upper Rasyan Valley, The formation of committees Sub-water basin to ensure the management of water resources from the lower level, Resolving water conflicts in different regions of the study area and the basin provider of water to the city of Taiz, Community participation by establishment of water users associations (WUAs) in the sub- basin areas.